Corporate Social Responsibility and Financial Profitability in the hotel sector of Cuenca – Ecuador - Arebalo-Naulaguari, Jaqueline Dayana; Tapia-Alvarez, Estefania Michelle; Armijos Cordero, Johanna Catalina; Fernández Aviles, Gladys Victoria (Estudios de Administración, 2021)
Socially responsible practices are applied as a business management strategy for the well-being of stakeholders and they contribute to the promotion of sustainable development processes (Villacís et al., 2016). The purpose of this article is to determine the relationship between Corporate Social Responsibility practices in the consumer area and the profitability of six lodging establishments in the city of Cuenca. The results showed a positive relationship between the CSR-Consumer Index and Return on Sales, and between the Customer Relationship criterion and Return on Sales. The lodging establishments involved in the study are clear that the greater the level of implementation of Corporate Social Responsibility, the higher the financial profitability. The study therefore provides new information for companies of developing countries and for a city considered as a microcosm.